Translocality: Concepts, Applications and Emerging Research Perspectives. Issue 5 (30th May 2013) - Greiner, Clemens; Sakdapolrak, Patrick
Abstract The employment of translocality as a research perspective is currently gaining momentum. A growing number of scholars from different research traditions concerned with the dynamics of mobility, migration and socio‐spatial interconnectedness have developed conceptual approaches to the term. They usually build on insights from transnationalism while attempting to overcome some of the limitations of this long‐established research perspective. As such, translocality is used to describe socio‐spatial dynamics and processes of simultaneity and identity formation that transcend boundaries—including, but also extending beyond, those of nation states. In this review, we trace the emergence of the idea of translocality and summarise the characteristics that different authors associate with the term. We elucidate the underlying notions of mobility and place and sketch out fields of research where the concept has been employed. On the basis of our findings, we conclude by proposing key areas where a translocal approach has the potential to generate fruitful insights. © 2012 The Author. Geography Compass © 2012 Blackwell Publishing Ltd